Responses of Invasive and Native Populations of the Seagrass Halophila stipulacea to Simulated Climate Change - Nguyen, Hung Manh; Yadav, Narendra Singh; Barak, Simon; Lima, Fernando P.; Sapir, Yuval; Winters, Gidon (Frontiers in Marine Science, 2020)
Climate change fuels invasions of plant species and displacement of local plants. Little is known about the ecophysiological adaptation of the invasive species, and their ability to cope with the changing conditions in their new habitat. Halophila stipulacea, a tropical seagrass native to the Gulf of Aqaba (GoA; northern Red Sea), became a Lessepsian migrant spreading within the eastern Mediterranean where it could potentially outcompete local species. We analyzed temperature records in the last 35 years and show that water temperature has increased faster in the eastern Mediterranean Sea compared to GoA, suggesting that H. stipulacea’s invasive success is associated with adaptation to thermal warming. Furthermore, we compared the responses of native (Eilat, Israel) and invasive (Limassol, Cyprus) H. stipulacea plants to current (26oC) and predicted thermal maxima (29℃ and 32℃) in a controlled experimental microcosm. Morphological and photo-physiological results showed negative effects of heat stress on the native plants while un-affected/ or even enhanced performance in their invasive counterparts. Gene expression, studied for the 1st time in H. stipulacea, pointed to differences in the molecular responses of two populations to thermal stress. Results predict that sea warming will cause vast reductions in H. stipulacea meadows growing in the GoA while sea warming will facilitate H. stipulacea’s spread within the Mediterranean Sea.